Fraud Triangle Analysis in Detecting Potential Fraud in Financial Statements: Analisis Fraud Triangle dalam Mendeteksi Potensi Kecurangan Terhadap Laporan Keuangan - Jayanti, Anisa; Nurasik, Nurasik (Indonesian Journal of Innovation Studies, 2022)
This studied aims to analyze fraudtriangle to potential fraudulent financial statement. Ffraudtriangle in this studied presure that proxieed by financial tarjet, finanecial need, external pressure, oportunity thats proxied by nature of industrie and inefective monitoring and rationalization thats proxied by auditor chanjes. This studied use F-score to investigation the potencial of fraudulent fiancial statements.The Populations in0this studied PT Garuda Indonesia list on the Indonesian Stock Exchanges 2017-2019. The studied use the multiples regresions for the analyss. The resulsts how thats only oportunity that proxied by inefective monitoring, nature of industrie, financial need and rationalization proved has significanta effects to the potencials of fraudulent financial statements. Meanwhile, financial tarjet and eksternal presure has no significants effects to fraudulent financial statements.